The structure of the verbal attic and its intervention in the process of deduction according to the schools of jurisprudence - Hussein Rajabi / Mustafa Zaki Yahya ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This article deals with the study of the basic rules of the verbal rules in the process of devising Islamic rule in Islamic jurisprudence schools. Attic rhetoric in the process of devising legitimacy when the schools of jurisprudence? The research included the study of some sub-questions, including: First: What is the law of reason and reason in the science of speech? What are its sections and divisions? Second: What is the role of reason and reason in the science of jurisprudence and the principles of jurisprudence when doctrines doctrine? Third: What are the applications of the cause and possible causes in the science of jurisprudence and the principles of jurisprudence? The research thus reached his hypothesis: the process of devising the Islamic rule in the doctrines of jurisprudence in many of its branches are affected, but may depend on what proves the attic verbal building is recognized, and this research is one of the expeditions of the origins of the entrance of the science of speech in the process of devising legitimacy, Written in accordance with an inductive analytical approach, this article